Extracranial-Intracranial Bypass (EC/IC) for Symptomatic Occlusive Cerebrovascular Disease Not Amenable to Carotid Endarterectomy A Case of Report (Medicine Today, 2012)
DOI: http://dx.doi.org/10.3329/medtoday.v23i2.13112 Medicine TODAY Vol.23(2) 2011 pp.109-111